Modeling Interactions between Liposomes and Hydrophobic Nanosheets. Issue 6 (27th December 2018) - Li, Zhen; Zhang, Yonghui; Ma, Jiale; Meng, Qiangqiang; Fan, Jun
Abstract : 2D nanomaterials could cause structural disruption and cytotoxic effects to cells, which greatly challenges their promising biomedical applications including biosensing, bioimaging, and drug delivery. Here, the physical and mechanical interaction between lipid liposomes and hydrophobic nanosheets is studied utilizing coarse‐grained (CG) molecular dynamics (MD) simulations. The simulations reveal a variety of characteristic interaction morphologies that depend on the size and the orientation of nanosheets. Dynamic and thermodynamic analyses on the morphologic evolution provide insights into molecular motions such as "nanosheet rotation, " "lipid extraction, " "lipid flip‐flop, " and "lipid spreading." Driven by these molecular motions, hydrophobic nanosheets cause morphologic changes of liposomes. The lipid bilayer structure can be corrugated, and the overall liposome sphere can be split or collapsed by large nanosheets. In addition, nanosheets embedded into lipid bilayers greatly weaken the fluidity of lipids, and this effect can be cumulatively enhanced as nanosheets continuously intrude. These results could facilitate molecular‐level understanding on the cytotoxicity of nanomaterials, and help future nanotoxicology studies associating computational modeling with experiments. Abstract : Molecular dynamics simulations are performed to investigate the physical interaction between hydrophobic nanosheets and lipid liposomes. Depending on the nanosheet size and orientation, hydrophobic nanosheets and liposomes could form a variety of characteristic interaction states. Molecular motions that drive the morphologic changes, dynamic details, and thermodynamics are explored, which uncover important knowledge on the behavior of 2D nanomaterials in biosystems.